2017
DOI: 10.2147/ppa.s131496
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication practice in Ethiopia: a systematic review

Abstract: BackgroundSelf-medication patterns vary among different populations, and are influenced by many factors. No review has been done that comprehensively expresses self-medication practice in Ethiopia. The aim of this study was to provide an overview of the literature on self-medication practice in Ethiopia.Materials and methodsDatabases (PubMed, Google Scholar, ResearchGate, and Hinari) were searched for published studies on the practice of self-medication in Ethiopia without restriction in the year of publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(184 citation statements)
references
References 49 publications
9
162
0
13
Order By: Relevance
“…As per the Health Belief Model, a cue to action by mothers/caregivers influenced by the medical personnel, family and friends contributed to use of antibiotics without prescription which may contribute to antibiotic resistance. Other researchers established that these drugs are mostly bought from drug-retail outlets under the prescription of a pharmasist or a friend (Shafie et al, 2018;Ayalew, 2017;Bachrach and Gardner, 2002). These findings are in agreement with available published literature which indicated that intentions for selfmedication with antibiotics result from the need to save money and the desire to act promptly to treat suspected or confirmed bacterial infections (Carvajal-Vélez et al, 2016;Chalovich and Eisenberg, 2013;Le et al, 2011).…”
Section: Determinants Of Antimicrobial Use In Diarrhoea Managementsupporting
confidence: 65%
See 1 more Smart Citation
“…As per the Health Belief Model, a cue to action by mothers/caregivers influenced by the medical personnel, family and friends contributed to use of antibiotics without prescription which may contribute to antibiotic resistance. Other researchers established that these drugs are mostly bought from drug-retail outlets under the prescription of a pharmasist or a friend (Shafie et al, 2018;Ayalew, 2017;Bachrach and Gardner, 2002). These findings are in agreement with available published literature which indicated that intentions for selfmedication with antibiotics result from the need to save money and the desire to act promptly to treat suspected or confirmed bacterial infections (Carvajal-Vélez et al, 2016;Chalovich and Eisenberg, 2013;Le et al, 2011).…”
Section: Determinants Of Antimicrobial Use In Diarrhoea Managementsupporting
confidence: 65%
“…This delay in medication provides a leeway for faster becterial multiplication which prolongs the time taken for the child to recover from diarrhoea and may affect its survival. This implies that their ability to detect diarrhoeal disease which in turn affects their response rate is low, such that some mothers/caregivers percieve diarrhoea as mild medical condition which does not warrant seeking medical care (Le et al, 2011;Ayalew, 2017).…”
Section: Management Of Diarrhoea Casesmentioning
confidence: 99%
“…The practice is expected to be higher in developing countries like Ethiopia this may be due to limited number of health care facilities available to the public. Self-medication is also expected to be even more practiced among health science students, who differed from the general population because they were exposed to knowledge about diseases and drugs, so they might be expected to behave differently [14]. Self-medication practice is prevalent in Ethiopia and varies in different populations and regions of the country [15].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the prevalence of SMP is inconsistent ranging from 32.5 to 81.5% [24]. In Ethiopia, the prevalence of self-medication practice ranges from 12.8% to 77.1% [5]. …”
Section: Introductionmentioning
confidence: 99%